PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA PEGAWAI KANTOR BADAN KEUANGAN DAERAH KABUPATEN PAMEKASAN - jurnalmap map; Pahrianto ÔÇÄ; Chamariyah ÔÇÄ (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
This research was conducted at the Regional Financial Board of Pamekasan Regency with a total sample of 62 people. The research objective was to see, describe and test the influence both partially and simultaneously on leadership style, work discipline, Organizational Citizenship Behavior and employee performance of the Regional Financial Board in Pamekasan Regency. This type of research is an explanatory study with a quantitative approach. The results showed that simultaneously, leadership style, work discipline, and organizational citizenship behavior have a very significant influence on employee performance. Partially, leadership style, work discipline, and organizational citizenship behavior have a significant effect on the performance of the Pamekasan Regency Regional Finance Agency employees, thus all independent variables partially have a significant effect on the performance of the Pamekasan Regency Regional Finance Agency employees. The variable of work discipline has an influence on the performance of the employees of the Regional Finance Agency in Pamekasan Regency. Keywords: leadership style, work discipline, organizational citizenship behavior, employee performance